Pengaruh Human Capital dan Spiritual Capital Terhadap Kinerja Pegawai di Kantor Camat - Sri Maryati Tune (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2024)
This research was conducted with the aim of knowing and analyzing the influence of human capital on employee performance at the Central City District Head Office, Gorontalo City; knowing and analyzing the influence of spiritual capital on employee performance at the Central City Subdistrict Office, Gorontalo City; determine and analyze the influence of human capital and spiritual capital together on employee performance at the Central City District Head Office, Gorontalo City. The analytical method used is a quantitative data analysis method, using a multiple linear regression model. The research population was all employees of the Central City District Head Office, 38 people using purposive sampling, 38 people were obtained using census techniques. The results of the research show that in partial testing, Human Capital and Spiritual Capital have a significant effect on employee performance at the Central City District Head Office. The results of simultaneous calculations show that the Fcount value of 327.063 is greater than the Ftable value of 3.259 with a significance level of F of 0.000 which is a value smaller than 0.05, so it can be concluded that together Human Capital and Spiritual Capital have a significant influence on employee performance at the City District Head Office. Middle. For the Adjusted R Square value of 0.944, it means that 94.4% of the two independent variables Human Capital and Spiritual Capital together can explain the model of this research and the remaining 5.6% is explained by other variables or factors that were not studied.